Relative contributions of nine genes in the pathway of histidine biosynthesis to the control of free histidine concentrations in Arabidopsis thaliana - Rees, J; Ingle, R; Smith, J (2009)
Despite the functional importance of histidine (His) as an essential amino acid in proteins and as a metal-coordinating ligand, comparatively little is known about the regulation of its biosynthesis in plants and the potential for metabolic engineering of this pathway. To investigate the contribution of different steps in the pathway to overall control of His biosynthesis, nine His biosynthetic genes were individually over-expressed in Arabidopsis thaliana to determine their effects on free amino acid pools. Constitutive, CaMV 35S-driven over-expression of the cDNAs encoding either isoform of ATP- phosphoribosyltransferase (ATP-PRT), the first enzyme in the pathway, was sufficient to increase the pool of free His by up to 42-fold in shoot tissue of Arabidopsis, with negligible effect on any other amino acid. In contrast, over-expression of cDNAs for seven other enzymes in the biosynthetic pathway had no effect on His content, suggesting that control of the pool of free His resides largely with ATP-PRT activity. Over-expression of ATP-PRT and increased His content had a negative pleiotropic effect on plant biomass production in 35S:PRT1 lines, but this effect was not observed in 35S:PRT2 lines. In the presence of 100 μM Ni, which was inhibitory to wild-type plants, a strong positive correlation was observed between free His content and biomass production, indicating that the metabolic cost of His overproduction was outweighed by the benefit of increased tolerance to Ni. His-overproducing plants also displayed somewhat elevated tolerance to Co and Zn, but not to Cd or Cu, indicating chemical selectivity in intracellular metal binding by His. © 2009 Blackwell Publishing Ltd.